The Concept of Marriage in the Holy Qur’an According to Sayyid Qutb in Fī Ẓilāl al-Qur’ān: A Study in Confronting the Phenomenon of “Marriage is Scary”: "مفهوم الزواج في القرآن الكريم عند سيد قطب في ظلال القرآن: دراسة في مواجهة ظاهرة "الزواج مخيف - Ahmad Fadly Rahman Akbar; Lulu’atul Fuad (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The phenomenon of “Marriage is Scary” has become one of the growing social issues among today’s young Muslim generation. Fear of marriage arises from past traumas, economic concerns, and the influence of individualistic culture that weakens the spiritual values and meaning of marriage. This research aims to reveal how Sayyid Qutb interprets the Qur’anic verses on marriage and how his ideas can respond to the “Marriage is Scary” phenomenon. This study is a thematic research employing a literature review, descriptive, and analytical methods. In other words, after describing the interpretations of Qur’anic verses containing commands to marry from various classical exegetes, the researcher correlates them with the current spiritual and moral challenges faced by today’s generation. The results show that Sayyid Qutb’s thought provides a comprehensive response to the “Marriage is Scary” phenomenon through three main aspects. First, in QS. Ar-Rūm [30]: 21, the principle of marriage emphasizes the importance of faith, responsibility, and spiritual balance as the foundation for achieving tranquility (sakinah). Second, in QS. An-Nisā’ [4]: 34, the purpose of marriage is presented as a means of moral and spiritual development that nurtures love (mawaddah) and mercy (rahmah). Third, in QS. An-Nūr [24]: 32, the command to marry is understood as an act of obedience to Allah that can heal trauma and strengthen faith. Thus, Sayyid Qutb’s ideas can serve as a spiritual alternative solution to the crisis of the meaning of marriage in the modern era. Upon completing this study, the researcher suggests that future studies expand the analysis by comparing Sayyid Qutb’s views with other contemporary exegetes, or by examining the “Marriage is Scary” phenomenon through multidisciplinary approaches such as Islamic psychology and the sociology of religion, to enrich both spiritual and social perspectives on this issue.